A new species of the genus Gonioctena (Coleoptera: Chrysomelidae: Chrysomelinae) from Shikoku, Japan, with description of its immature stages - Suenaga, Haruki (Zootaxa, 2012)
The adult, pupa, and larva of Gonioctena (Gonioctena) iyonis n. sp. are described from Shikoku, Japan. This species is similarto G. (G.) hiranoi Takizawa, G. (G.) simotuke Takizawa, G. (G.) hoki Takizawa and G. (G.) katsuyai Takizawa, and is distin-guished from them by the coloration of the femora and the shape of the aedeagus. The host plant of G. (G.) iyonis n. sp. is Alnus firma Siebold et Zucc.